Analisis Penegakan Hukum dengan Penggunaan Alat Bukti dalam Pemeriksaan Perkara Minyak Goreng No. 15/Kppu-I/2022 - Meylani Anggraini; Richard C. Adam (LPPM Universitas Ekasakti Padang, 2023)
This research discusses the use of evidence, including circumstantial evidence, in the process of examining the Cooking Oil case No. 15/KPPU-I/2022 by the Business Competition Supervisory Commission (KPPU). This case involves alleged cartel practices in the cooking oil industry in Indonesia. This research aims to analyze the extent to which indirect evidence contributes to proving cartel practices in this case and how this evidence is used in law enforcement. The research method used is an in-depth case study, by collecting and analyzing data from various relevant sources. The research results show that indirect evidence plays an important role in building cases of cartel practices and contributes significantly to the enforcement of business competition law. The KPPU's decision in this case was supported by strong evidence, and the use of circumstantial evidence has helped uncover violations of business competition law. This decision has a direct impact on business competition practices in the cooking oil industry and encourages compliance with business competition laws in the future